Heutagogy-Based Training Management: Self-Determined Learning for Adult Learners - Imsiyah, Niswatul; Sintiawati, Nani; Purnamawati, Frimha; Himmah, Irliana F (JPPM (Jurnal Pendidikan dan Pemberdayaan Masyarakat), 2024)
Heutagogy-based training management emphasizes learner autonomy, adaptability, and self-motivation"”making it especially relevant for adult learners in non-formal educational settings. This study explores how self-determined learning is implemented in a heutagogical framework at the Course and Training Institute (LKP) in Jember Regency. Guided by four core principles"”self-efficacy, self-determination, self-directed learning, and self-regulated learning"”heutagogy enables participants to engage more meaningfully with learning content, develop real-world competencies, and cultivate lifelong learning skills. Using a qualitative approach, this research employed observation, in-depth interviews, and documentation studies to gain a comprehensive understanding of the training experience. The study was conducted at LKP in Sumbersari District, selected through purposive sampling. Data analysis followed an interactive model consisting of data collection, reduction, display, and verification. Data validity was ensured through prolonged engagement, persistent observation, and triangulation of sources and methods. The findings show that participants demonstrate strong autonomy in determining their learning goals and strategies, competence through hands-on practice and feedback, and relatedness through collaborative peer interaction. These findings reinforce the importance of heutagogy-based training in promoting independent, motivated, and socially connected adult learners.